Conhecendo a vida da galinha - Teles, Antonio Miguel Bianco; Bento, Miriam Furtado; Schiavinato, Ricardo Leandro; Lima, Eliene Xavier de; Simião, Regina (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf